Narrativas tecnológicas, desenraizamento e cultura de resistência: história oral de vida de famílias desapropriadas pela construção da Usina Hidrelétrica de Itaipu - Matiello, Catiane (2011)
The dissertation aimed to understand the practices, representations and the meanings constructed about the process of implementation of the hydroelectric plant of Itaipu, in the West of Paraná, during the 70’s and the 80’s, by the agriculture women and men who lived this reality through the dispossessing process. The theoretical assumption which has orientated this work is constituted by the Field of Social History and by the Science, Technology and Society one as well, translated into the valuing of the experience of the subjects in the development technological process. The methodological approach used for the field research was the oral life history and resulted in the register of eleven interviews, which form a history of the daily routine of the dispossessing process. The analysis tried to throw some light on the social dimension present and constituting the interviews, valuing the converging answers, and taking into consideration the way in which each individual perceived the changes. Its realization took place from the noticed themes, organized into three sections, which highlight the narrative as a construction which involves experience and memory and which brings representations, social and individual practices. In the first section, “Technological narratives”, we have analyzed the role of the representations of technology in the technological narratives and in the adoption of celebrating positions around of the construction of the hydroelectric plant by the collaborators. These representations are related to the hegemonic representations about the construction of the Itaipu plant, in a way that the analysis of the articulations between them took place through the incorporation of the documents (newspapers, magazines, and texts for radio programs) which are part of the official narratives. The second section, “Uprooting Narratives”, has analyzed the meaning construction around dispossession. The narratives have pointed the land as a fundamental element, which associate a community life deeply integrated, through neighborhood and kinship relations, in a way that the rooting exceeds the forms of survival created to conform the realization of a life project. In the last section of this chapter, entitled “Narratives of resistance”, the resistance of the dispossessed was emphasized, in the organized form of the Justice Movement and Lands as well as in the private space, in the case of the women’s narratives. We have noticed that religion and the solidarity relations of the community were used in the legitimation and sustenance of the struggle and that in the formation of a resistance culture, the collaborators noticed the power relations involved in the construction of the hydroelectric plant, as well as the economical and political choices, in a way that the concepts of technology characterized by neutrality, determinism and inexorability started being questioned.